Genome-wide identification of epigenetic regulators in Quercus suber L. - Silva, Helena G. (2020)
Modifications of DNA and histones, including methylation and acetylation, are critical for the epigenetic regulation of gene expression during plant development, particularly during environmental adaptation processes. However, information on the enzymes catalyzing all these modifications in trees, such as Quercus suber L., is still not available. In this study, eight DNA methyltransferases (DNA Mtases) and three DNA demethylases (DDMEs) were identified in Q. suber. Histone modifiers involved in methylation (35), demethylation (26), acetylation (8), and deacetylation (22) were also identified in Q. suber. In silico analysis showed that some Q. suber DNA Mtases, DDMEs and histone modifiers have the typical domains found in the plant model Arabidopsis, which might suggest a conserved functional role. Additional phylogenetic analyses of the DNA and histone modifier proteins were performed using several plant species homologs, enabling the classification of the Q. suber proteins. A link between the expression levels of each gene in different Q. suber tissues (buds, flowers, acorns, embryos, cork, and roots) with the functions already known for their closest homologs in other species was also established. Therefore, the data generated here will be important for future studies exploring the role of epigenetic regulators in this economically important species.